Public and Professional Discussion on the Results of the Updated Content of Subject Education: Approaches in Primary General and Basic General Education - Arinushkina, Anna; Dovbysh, Svetlana (Journal of History Culture and Art Research, 2019)
The paper focuses on the updated content of subject education in Russia, discussing its outcomes among the general public and in professional circles. Thus, the topic is of high importance due to the need to obtain both the feedback and scientific synthesis of expert and professional discussions on the updated content of general education. The article analyzes foreign experience in modernization of educational standards, considers the specifics of changes and public discussions of the Federal State Educational Standard (FSES) (primary general and basic general education), public discussions of the contemporary FSES are considered as a decision-making mechanism taking into account specifics of the features of general education in Russia. The conducted research clearly demonstrates that a controversial situation has arisen: a low quality of education, a lack of transparent requirements for the content and results of education, a low level of expectations imposed on most students, leading to deep contradictions between the tasks facing the modern school. The research also shows that the educational standardization has become one of the most dynamically developing areas of educational reforms and the main trend in the development of education systems.